New records of Hierodula transcaucasica Brunner von Wattenwyl, 1878 (Mantodea) from Bulgaria - Boyan Zlatkov; Stanislav Stefanov; Victor Gashtarov; Vladislav Vergilov (Historia naturalis bulgarica, 2020)
New localities of Hierodula transcaucasica Brunner von Wattenwyl, 1878 from Bulgaria and illustrations of the species are provided.